Patologi Sosial Prostitusi Anak Dan Perdagangan Manusia: Kajian Patologi Sosial Dalam Perspektif Hak Asasi Manusia - Aurellya Ramadhani Syainda Putri; Khansa Athaya Nurulkamila; Khinalya Farradiba Syahnaz; Tasya Amanda Putri; Wevy Efticha Sary (GLOBAL SCIENTS PUBLISHER, 2025)
Child prostitution tied to human trafficking stands out as one of the gravest and most intricate social issues plaguing Indonesia. It highlights the extreme susceptibility of children to sexual abuse while revealing underlying societal flaws, such as widespread poverty, inadequate educational opportunities, crumbling family units, and the decline of ethical and communal standards. As outlined in the document, this exploitation occurs via multiple methods, including luring victims with deceptive job offers, transporting them between locations, abusing them in local brothels or entertainment spots, and newer trends like online solicitation via social media and secure digital channels. These operations typically involve coordinated groups of recruiters, middlemen, exploiters, and clients. Viewed through a human rights lens, child prostitution is a serious infringement on children's basic dignity and rights, as protected by the Convention on the Rights of the Child (CRC), Indonesia's Child Protection Law, and the Anti-Human Trafficking Law. Affected children are deprived of safeguards, schooling, healthcare, safety, and the chance to mature normally. The discussion stresses the government's duty to uphold, safeguard, and ensure these rights, yet execution is hindered by ineffective policing, poor collaboration among agencies, and insufficient support for victim recovery and reintegration. The study determines that child prostitution within human trafficking reflects a breakdown in societal structures and shortcomings in child welfare systems. Consequently, a comprehensive strategy is imperative, combining prevention via education and financial support, rigorous prosecution of trafficking rings, and thorough rehabilitation for survivors. Reinforcing compassionate principles and widespread societal consciousness is crucial to ending the cycle of abuse and securing complete rights-based protection for children.